Heterogeneity of ILC2s in the Lungs - Asaoka, Masato; Kabata, Hiroki; Fukunaga, Koichi (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) are GATA3-expressing type 2 cytokine-producing innate lymphocytes that are present in various organs throughout the body. Basically, ILC2s are tissue-resident cells associated with a variety of pathological conditions in each tissue. Differences in the tissue-specific properties of ILC2s are formed by the post-natal tissue environment; however, diversity exists in ILC2s within each tissue due to developmental timing and activation states. Such diversity of steady-state and activated ILC2s has been clarified with the advancement of single-cell RNA-seq technology, and has gradually been revealed in mice and humans. Another component of complexity is that ILC2s can acquire other ILC-like functions, depending on the lung environment. Further, ILC2s having immune memory and exhausted ILC2s are present in vivo, and the nature of ILC2s varies with senescence. To clarify how the diversity of ILC2s affects human diseases, it is necessary to conduct research based on a comprehensive understanding of ILC2s that considers the diversity of ILC2s, rather than a snapshot of a single section. In this review, we summarize the current understanding of the heterogeneity of ILC2s in the lungs and hope to highlight a novel field of immunology.